Benthic ostracoda and foraminifera from the North Adriatic Sea (Italy, Mediterranean Sea): A proxy for the depositional characterisation of river-influenced shelves - Barbieri, Giulia; Rossi, Veronica; Vaiani, Stefano Claudio; Horton, Benjamin Peter (Marine micropaleontology, 2019)
We investigated the distribution of ostracoda and benthic foraminifera from the shallow (<40 m water depth) river-influenced North Adriatic shelf. Combining faunal and environmental data from a sub-set of literature databases (Breman, 1975; Jorissen, 1988), we recognised the main environmental drivers for ostracoda (grain-size and bathymetry) and benthic foraminifera (organic matter concentration). Integrating these benthic groups, we identified five depositional settings dependent on the relative position from the main source of riverine material: the Po River. Near the Po Delta, where high fluxes of sediment occur, taxa tolerant to organic-rich muddy substrates and oxygen deficiency are abundant (Palmoconcha turbida, Leptocythere ramosa, Ammonia tepida, Ammonia parkinsoniana, Nonionella turgida). Downdrift of the delta, ostracoda discriminate between shallow sandy substrates (Semicytherura incongruens, Xestoleberis spp.) subject to longshore currents and deeper clayey environments (S. incongruens, Palmoconcha turbida), whereas benthic foraminifera are monotonous being represented by taxa tolerant to moderate organic matter concentrations (A. parkinsoniana, A. tepida, Aubignyna perlucida). The mud-loving Cytheridea neapolitana and Bulimina denudata, tolerating high organic matter fluxes, characterise the 20–40 m deep mud-belt subject to the major accumulation of riverine material. Updrift, sandy substrates with low organic matter are typified by S. incongruens, Pontocythere turbida and Milioloidea. Out of the fluvial influence (water depth > 20 m), diversified meiofaunal assemblages occur with ostracoda discriminating sediment-starved areas enriched in sand. Our results demonstrate that the combined use of ostracoda and benthic foraminifera represents a powerful tool for the depositional characterisation of river-influenced shelves and to achieve detailed palaeogeographical reconstructions from shallow marine successions. •Integration of ostracoda and benthic foraminifera from the North Adriatic shelf•Ostracoda and benthic foraminifera respond to distinct environmental drivers•Combine meiofauna to detect and refine river-influenced depositional environments